Walt Disney's Winnie the Pooh and Tigger too (Random House, 1975)
Rabbit plans to unbounce Tigger, but he discovers he likes a bouncy Tigger best
Keywords: Friendship / Juvenile fiction; Friendship / Fiction; Amitié / Romans, nouvelles, etc. pour la jeunesse; Friendship; Picture books; Fictional Work; Children's stories; Fiction; Juvenile works; Romans; Bilderbuch